Acute Unilateral Renal Infarction in the Setting of an Inherited Thrombophilia and Atrial Septal Defect. (27th August 2017) - Piran, Siavash; Schulman, Sam
Abstract : We present a case of renal infarction in a 43-year-old female with history of stroke at age 14. She was found to be heterozygous for the prothrombin G20210A gene mutation. Loop monitoring revealed no atrial fibrillation. Transthoracic and transesophageal echocardiograms showed no thrombus. However, there was a small shunt due to an atrial septal defect (ASD). She was treated with warfarin and had device closure of her ASD. This was a suspected case of paradoxical embolism through an ASD leading to renal infarction.